Atrioventricular Dissociation following Blunt Chest Trauma - Salim Surani; Karen Allen; Cynthia Ocegueda-Pacheco; Joseph Varon (Case Reports in Medicine)
Blunt chest trauma (BCT) is a common clinical presentation seen in emergency departments. Few cases of cardiac conduction abnormalities due to BCT have been reported in the medical literature. This dysrhythmias may present as permanent conduction defects requiring permanent pacemaker or may have temporary conduction abnormalities requiring temporary pacemaker or supportive care. We present the case of a young woman who suffered from BCT after being kicked by a horse with the development of a significant substernal hematoma. She developed temporary atrioventricular block, which was completely resolved with the decrease in the size of the substernal hematoma suffered.